2021
DOI: 10.1038/s41380-021-01065-6
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 interferon mediates chronic stress-induced neuroinflammation and behavioral deficits via complement component 3-dependent pathway

Abstract: Chronic stress is a major risk factor in the pathophysiology of many neuropsychiatric disorders. Further, chronic stress conditions can promote neuroinflammation and inflammatory responses in both humans and animal models. Type I interferons (IFN-I) are critical mediators of the inflammatory response in the periphery and responsible for the altered mood and behavior. However, the underlying mechanisms are not well understood. In the present study, we investigated the role of IFN-I signaling in chronic stress-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 123 publications
1
20
0
Order By: Relevance
“…This pathway has been reported in immune diseases, such as multiple sclerosis (Li et al, 2021), Ig A nephropathy, and Henoch-Schönlein purpura nephritis (Fang et al, 2021). Complement activation has been demonstrated in previous reports (Roy et al, 2020;Tripathi et al, 2021) to be associated with type I interferon, which was significantly activated in DM and DM-ILD (Zhang et al, 2019a;de Jesus et al, 2020). These reports combined with our findings suggest direct and/or indirect links between the two pathways implicated in DM-ILD pathogenesis.…”
Section: Discussionsupporting
confidence: 87%
“…This pathway has been reported in immune diseases, such as multiple sclerosis (Li et al, 2021), Ig A nephropathy, and Henoch-Schönlein purpura nephritis (Fang et al, 2021). Complement activation has been demonstrated in previous reports (Roy et al, 2020;Tripathi et al, 2021) to be associated with type I interferon, which was significantly activated in DM and DM-ILD (Zhang et al, 2019a;de Jesus et al, 2020). These reports combined with our findings suggest direct and/or indirect links between the two pathways implicated in DM-ILD pathogenesis.…”
Section: Discussionsupporting
confidence: 87%
“…No statistical methods were used to predetermine sample sizes in the current study, but our sample sizes are similar to those reported in previous publications [ 24 , 25 ]. Data were presented as mean ± SEM.…”
Section: Methodsmentioning
confidence: 77%
“…Similarly, our earlier study found an increase in C3 mRNA levels in the prefrontal cortex (PFC) of depressed suicide subjects [ 23 ]. In addition, we found that inhibition of C3a signaling attenuates chronic stress-induced depressive-like behavior in mice [ 23 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…In vivo, we observed that the IFN-β mRNA expression in the prefrontal cortex was signi cantly decreased in RST mice compared with control mice, However, the serum IFN-β level was enhanced in RST mice. Consistently, recent study reported that serum IFN-β levels was increased in chronic stress mice, and systemic blockade of type interferons signaling attenuated chronic stress-induced in ltration of macrophages into prefrontal cortex and behavioral abnormalities [40]. The reason behind the differing levels in the brain or serum in chronic restraint stress is not clear.…”
Section: Discussionmentioning
confidence: 93%